SWOT ANALYSIS AS FORMULATION OF MARKETING STRATEGIES ON NOUGGY CULINARY BUSINESS IN MALANG CITY - Tri Utami, Lia Ujung; Evelina, Tri Yulistyawati (Transpublika Publisher, 2024)
This research aims to formulate effective marketing strategies for the